PKS 1018–42: A Powerful, Kinetically Dominated Quasar - Punsly, B.; Tingay, Steven (The American Astronomical Society, 2006)
We have identified PKS 1018-42 as a radio galaxy with extraordinarily powerful jets, over twice as powerful as any 3CR source of equal or lesser redshift except one (3C 196). It is perhaps the most intrinsically powerful extragalactic radio source in the still poorly explored southern hemisphere. PKS 1018-42 belongs to the class of FR II objects that are kinetically dominated; the jet kinetic luminosity, Q ~ 6.5 × 1046 ergs s-1 (calculated at 151 MHz), is 3.4 times larger than the total thermal luminosity (IR to X-ray) of the accretion flow, Lbol ~ 1.9 × 1046 ergs s-1. It is the fourth most kinetically dominated quasar that we could verify from existing radio data. From a review of the literature, we find that kinetically dominated quasars such as PKS 1018-42 are rare, and we list the five most kinetically dominated sources found from our review. Our results for PKS 1018-42 are based on new observations from the Australia Telescope Compact Array.